The Role of Mosque-Based Non-Formal Islamic Education in Building Sakinah Families - Katni, Katni; Sumarni, Sri; Muslim, Aziz (Letiges, 2022)
This research aims to describe the role of mosque-based non-formal Islamic education in forming a sakinah family. This research is field research with a qualitative paradigm. The location selection was made purposively. Data collection techniques through interviews, observation and documentation. Data analysis uses an analytical descriptive model. The role of mosque-based non-formal Islamic education in forming a sakinah family is analyzed using Kuntowijoyo's prophetic social science approach. The results of the study are: 1) Mosque-based non-formal Islamic education plays a strategic and significant role in forming a sakinah family in the process of humanization, liberation and transcendence in the formation of a sakinah family, and also plays a role as an adult education effort in solving the problem of forming a sakinah family; 2) The results of the role of non-formal Islamic education in the mosque can increase individual, semi-social and collective humanization in the formation of a sakinah family. They are improving knowledge system liberation, social system liberation, economic system liberation and political system liberation to form a sakinah family. The process of transcendence can increase the obedience of family members to religion and social norms and make the basis of humanization and liberation for forming a sakinah family.